Destructive Photon Echo Formation in Six‐Wave Mixing Signals of a MoSe2 Monolayer. Issue 1 (29th October 2021) - Hahn, Thilo; Vaclavkova, Diana; Bartos, Miroslav; Nogajewski, Karol; Potemski, Marek; Watanabe, Kenji; Taniguchi, Takashi; Machnikowski, Paweł; Kuhn, Tilmann; Kasprzak, Jacek; Wigger, Daniel
Abstract: Monolayers of transition metal dichalcogenides display a strong excitonic optical response. Additionally encapsulating the monolayer with hexagonal boron nitride allows to reach the limit of a purely homogeneously broadened exciton system. On such a MoSe2 ‐based system, ultrafast six‐wave mixing spectroscopy is performed and a novel destructive photon echo effect is found. This process manifests as a characteristic depression of the nonlinear signal dynamics when scanning the delay between the applied laser pulses. By theoretically describing the process within a local field model, an excellent agreement with the experiment is reached. An effective Bloch vector representation is developed and thereby it is demonstrated that the destructive photon echo stems from a destructive interference of successive repetitions of the heterodyning experiment. Abstract : This is the first report of a destructive photon echo effect detected in a six‐wave mixing signal from the atomically thin semiconductor MoSe2 . By developing a sound theoretical model, it is shown that the effect is caused by the exciton‐exciton interaction in the material. It provides a new ultrafast spectroscopy tool to study the many‐particle interaction in 2D semiconductors.